Evaluation of Higher Secondary Education Curriculum Using the Context, Input, Process and Product Model in Rawalpindi Division, Pakistan - Asma, Shahzadi (2023)
Curriculum evaluation is an integral part of the educational process. Most curricula in Pakistan have often remained static for extended periods, hindering progress. Limited research has been conducted on the process of curriculum development in Pakistan in general and the higher secondary Education curriculum in particular. The current study aimed to fill this gap by evaluating the existing higher secondary Education curriculum in Pakistan using the CIPP (context, input, process, and product) evaluation model developed by Stufflebeam (1971). The purpose of this evaluation was to identify possible strengths and weaknesses of the Education curriculum in order to make necessary improvements. The population for the study consisted of teachers and students of the Education subject at the higher secondary level. A sequential explanatory mixed methods study was designed. Total population sampling was used to select the teachers, while simple random sampling technique was used for selecting the students. Data was collected through questionnaires and interviews. Descriptive statistics for quantitative data and thematic analysis for qualitative data was applied. The findings show that the textbook was the sole source of the subject content and there did not seem alignment between the curriculum and the textbook. This study found considerable inverse correlation among context, input, process and product as input is not according to the designed context, process is not effective that follows only theoretical traditional pedagogies and the learning outcomes do not fulfil the need of introducing this subject and moreover a gap of knowledge and implementation. This study has implications for bridging the gaps from planning to necessary revisions and improvements in the elements of Education curriculum. By working together, all the stakeholders can design a high quality Education curriculum that prepares students for choosing the teacher education, developing higher-order thinking skills, moving beyond rote memorization, emphasizing deeper learning, development of psychomotor skills and students’ growth for problem solving skills to face the challenges for success in the 21st century.